Absence of antibody responses to SARS-CoV-2 N protein in COVID-19 vaccine breakthrough cases. Issue 21 (November 2022) - Vu, Luan D; Wallace, Shonta; Phan, Anh TQ; Christofferson, Rebecca C; Turner, Erik; Parker, Sean; Elkind-Hirsch, Karen; Landry, Darrell; Stansbury, Austin; Rose, Rebecca; Nolan, David J; Lamers, Susanna L; et al.
Understanding the risk factors for breakthrough coronavirus disease 2019 (COVID-19) (BC19) is critical to inform policy. Herein, we assessed Delta (Lineage B.1.617.2) variant-specific effectiveness of the BNT162b2 (Pfizer) vaccine and characterized Delta-driven BC19 cases (fully vaccinated individuals who get infected) with known-time-since-vaccination. In this longitudinal prospective study (January 21–October 30, 2021), 90 naïve and 15 convalescent individuals were enrolled at the initiation of vaccination. Samples from 27 unvaccinated individuals with previous laboratory-confirmed COVID-19 diagnosis were collected at a single time point. Longitudinal serology profile (antibodies against severe acute respiratory syndrome coronavirus 2 [SARS-CoV-2] S and N proteins) and live-virus-based neutralization capacities were assessed while controlling for age. Sex, age, history of reactions to the COVID-19 vaccine, and viral neutralization capacities were identified as significant risk factors for breakthrough COVID-19. At 8 months postvaccination, male sex, individuals ⩾65 years of age, and individuals who experienced noticeable side effects with the COVID-19 vaccine were at 5.47 ( p- value = 0.0102), 4.33 ( p- value = 0.0236), and 4.95 ( p- value = 0.0159) fold greater risk of BC19 as compared to their peers, respectively. Importantly, every five-fold increase in viral neutralization capacities (by live-virus-based assays) was significantly associated with ~4-fold reduction in the risk occurrence of breakthrough COVID-19 ( p- value = 0.045). Vaccine boosting remarkably increased these viral neutralization capacities by 16.22-fold ( p- value = 0.0005), supporting the importance of the BNT162b2 booster in efforts to control the incursion of future variants into the population at large. Strikingly, BC19 cases exhibited a delayed/absent antibody response to the N protein, suggesting limited exposure to the virus. Since antibodies against N protein are widely used to evaluate the extent of virus spread in communities, our finding has important implications on the utility of existing serological diagnostic and surveillance for COVID-19.